HDPE Plastic and Glass Powder as Partial Sand and Cement Substitutes in Paving Blocks - Raymond Christ Opel Samosir; Anisah; Muh Abdhy Gazali (Universitas Medan Area, 2026)
The increasing use of paving blocks in parking areas and public facilities has increased the demand for durable and environmentally sustainable construction materials. Conventional paving block production, however, remains dependent on natural sand and cement. This study investigated the use of High-Density Polyethylene (HDPE) plastic as a 5% partial replacement for fine aggregate and glass powder (GP) as a partial cement replacement at levels of 10%, 15%, and 20%. A laboratory experimental method was employed using paving blocks measuring 21 cm × 10.5 cm × 6 cm with a cement-to-sand ratio of 1:3 and a water-cement ratio of 0.4. A total of 140 specimens were tested at 28 days for appearance and dimensions, compressive strength, water absorption, and abrasion resistance. The results showed that increasing GP content generally reduced compressive strength, particularly when combined with HDPE. The control mixture achieved the overall requirements for Quality B, whereas none of the HDPE-GP combinations satisfied all Quality B criteria simultaneously. The 5% HDPE + 10% GP mixture provided the most balanced performance, with a compressive strength of 20.03 MPa, while higher GP contents improved water absorption and abrasion resistance but reduced compressive strength. The findings indicate that HDPE and GP can be incorporated into paving blocks to support waste utilization and reduce dependence on conventional materials, although further optimization is required before large-scale application.